Weed dynamics and yield of fenugreek (Trigonella foenum-graecum) as influenced with irrigation levels and weed management practices - MEHTA, R S; PATEL, B S; MEENA, S S (The Indian Journal of Agricultural Sciences, 2010)
A field experiment was conducted during 2006–08 at Sardarkrushinagar to find out optimum irrigation level and weed management practices for getting higher yield of fenugreek (Trigonella foenum-graecum L.). Monocot weed at 40 days after sowing and at maturity as well as dicot and sedges weed population and dry weight of weeds at 40 days after sowing and at maturity and yield of fenugreek were exhibited significantly higher with irrigation at 1.0 irrigation water/cumulative pan evaporation ratio, followed by 0.8 ratio. Besides weedy check, the highest dry weight and population of weeds at 20 days after sowing was recorded by hand weeding at 20 and 40 days after sowing and hand weeding at 20 days after sowing + inter-culturing at 40 days after sowing but at 40 days after sowing the highest weed population and dry weight was recorded with pre-emergence application of pendimethalin 0.75 kg/ha and pendimethalin 0.75 kg/ha + interculturing at 40 days after sowing and at maturity the lowest dicot and sedge population was recorded by preemergence application of pendimethalin 0.75 kg/ha + interculturing at 40 days after sowing but lowest monocot weed population and dry weight of weed was recorded with hand weeding at 20 and 40 days after sowing. Besides, weedy check, the highest weed control efficiency at 20 days after sowing was recorded with pendimethalin 0.75 kg/ha + interculturing at 40 days after sowing but at 40 days after sowing and maturity the highest weed control efficiency was observed with hand weeding at 20 and 40 days after sowing.